Underrepresented racial minorities in biomedical informatics doctoral programs: graduation trends and academic placement (2002–2017). (14th October 2020) - Wiley, Kevin; Dixon, Brian E; Grannis, Shaun J; Menachemi, Nir
Abstract: Objective: Biomedical informatics attracts few underrepresented racial minorities (URMs) into PhD programs. We examine graduation trends from 2002 to 2017 to determine how URM representation has changed over time. We also examine academic job placements by race and identify individual and institutional characteristics associated with URM graduates being successfully placed in academic jobs. Materials and Methods: We analyze a near census of all research doctoral graduates from US-accredited institutions, surveyed at graduation by the National Science Foundation Survey of Earned Doctorates. Graduates of biomedical informatics-related programs were identified using self-reported primary and secondary disciplines. Data are analyzed using bivariate and multivariable logistic regressions. Results: During the study period, 2426 individuals earned doctoral degrees in biomedical informatics-related disciplines. URM students comprised nearly 12% of graduates, and this proportion did not change over time (2002–2017). URMs included Hispanic (5.7%), Black (3.2%), and others, including multi-racial and indigenous American populations (2.8%). Overall, 82.3% of all graduates accepted academic positions at the time of graduation with significantly more Hispanic graduates electing to go into academia (89.2%; P < .001). URM graduates were more likely to be single (OR = 1.38; P < .05), have a dependent (1.95; P < .01), and not receive full tuition remission (OR = 1.37; P = .05) as a student. URM graduates accepting an academic position were less likely to be a graduate of a private institution (OR = 0.70; P < .05). Discussion and Conclusion: The proportion of URM candidates among biomedical informatics doctoral graduates has not increased over time and remains low. In order to improve URM recruitment and retention within academia, leaders in biomedical informatics should replicate strategies used to improve URM graduation rates in other fields.